Generation of an induced pluripotent stem cell line (PNUYHi003-A) from peripheral blood mononuclear cells of a patient with neuronal intranuclear inclusion disease - Tae-Yun Kim; Mi Kyoung Kim; Takeshi Mizuguchi; Naomichi Matsumoto; Jae-Hyeok Lee; Eun-Joo Kim; Na-Yeon Jung (Stem Cell Research)
Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disorder characterized by eosinophilic hyaline intranuclear inclusions in the nervous system. NIID is associated with GGC repeat expansions in the 5′ untranslated region of the NOTCH2NLC gene. The induced pluripotent stem cells (iPSC), generated from peripheral blood mononuclear cells of a 75-year-old male patient with NIID, exhibited stem cell marker expression, normal karyotype, absence of viral factors, successful differentiation into the three germ layers, and were analyzed for GGC repeat expansion. These patient-derived iPSCs have promising potential for exploring the genetic mechanisms underlying NIID.